2021
DOI: 10.1039/d1dt01706c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into defect chemistry and tailored photoluminescence and photocatalytic properties of aliovalent cation substituted Zn0.94M0.06−xLixO (M: Fe3+, Al3+, Cr3+) nanoparticles

Abstract: In this work, we demonstrate the microwave assisted solution combustion synthesis of aliovalent cations substituted Zn0.94M0.06-xLixO (M: Fe3+, Al3+, Cr3+) nanoparticles. The structural features, photoluminscent and photocatalytic properties were characterized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The results showed that the photodegradation efficiencies of CZO (6 mol% Gr 3+ -doped ZnO), AZO (6 mol% Al 3+ -doped ZnO), and L3AZO (1.5 mol% Li + -ion co-doped AZO) catalysts were higher compared with the photodegradation efficiencies of ZnO catalysts (89%). 66 Kanithan et al group used nickel nitrate, iron nitrate, and magnesium nitrate as oxidants and arginine as fuel to synthesize undoped nickel ferrite spinel (NiFe 2 O 4 ) and magnesium doped nickel ferrite spinel (Ni 1− x Mg x Fe 2 O 4 ). The undoped NiFe 2 O 4 has a single-phase cubic spinel structure with an average crystallite size between 20 and 35 nm, while the magnesium-doped NiFe 2 O 4 also has a cubic spinel structure.…”
Section: Microwave-induced Combustion Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…The results showed that the photodegradation efficiencies of CZO (6 mol% Gr 3+ -doped ZnO), AZO (6 mol% Al 3+ -doped ZnO), and L3AZO (1.5 mol% Li + -ion co-doped AZO) catalysts were higher compared with the photodegradation efficiencies of ZnO catalysts (89%). 66 Kanithan et al group used nickel nitrate, iron nitrate, and magnesium nitrate as oxidants and arginine as fuel to synthesize undoped nickel ferrite spinel (NiFe 2 O 4 ) and magnesium doped nickel ferrite spinel (Ni 1− x Mg x Fe 2 O 4 ). The undoped NiFe 2 O 4 has a single-phase cubic spinel structure with an average crystallite size between 20 and 35 nm, while the magnesium-doped NiFe 2 O 4 also has a cubic spinel structure.…”
Section: Microwave-induced Combustion Synthesis Of Nanomaterialsmentioning
confidence: 99%
“…Even though both are effectively used, ZnO NPs are generally a better candidate for photocatalytic degradation of pollutants because of their high stability, non-toxicity, 15 single oxidation state, natural abundance, suitable band gap 16 and better biocompatibility. 17 ZnO is a wide bandgap (3.37 eV) 18 semiconductor which acts as an excellent photocatalyst for the decomposition of water pollutants. 19 One of the top most priorities of the present-day research is for clean water in order to retain the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor nanostructures have greatly contributed to the growth of nanotechnology due to their high surface to volume ratio and tunable band gap. 34 This attractive class of materials has been used in many functional nanodevices including sensors, 35,36 transistors, 37 solar cells, 38 electrocatalysts, 39 photocatalysts, 40,41 adsorbents, 42,43 and nanogenerators. 44 The working of thermoelectric devices is based on three effects, namely, the Seebeck effect, 45 Peltier effect, 46 and Thomson effect.…”
Section: Introductionmentioning
confidence: 99%